Metagenome-guided culturomics for the targeted enrichment of gut microbes - Jeremy Armetta; Simone S. Li; Troels Holger Vaaben; Ruben Vazquez-Uribe; Morten O. A. Sommer (Nature Communications)
Abstract The gut microbiome significantly impacts human health, yet cultivation challenges hinder its exploration. Here, we combine deep whole-metagenome sequencing with culturomics to selectively enrich for taxa and functional capabilities of interest. Using a modified commercial base medium, 50 growth modifications were evaluated, spanning antibiotics, physico-chemical conditions, and bioactive compounds. Whole-metagenome sequencing identified medium additives, like caffeine, that enhance taxa often associated with healthier subjects (e.g., Lachnospiraceae, Oscillospiraceae, Ruminococcaceae). We also explore the impact of modifications on the composition of cultured communities and establish a link between medium preference and microbial phylogeny. Leveraging these insights, we demonstrate that combinations of media modifications can further enhance the targeted enrichment of taxa and metabolic functions, such as Collinsella aerofaciens, or strains harboring biochemical pathways involved in dopamine metabolism. This streamlined, scalable approach unlocks the potential for selective enrichment, advancing microbiome research by understanding the impact of different cultivation parameters on gut microbes.